PERATURAN DAERAH ( PERDA ) SYARI’AH DAN PERDA BERNUANSA SYARI’AH DALAM KONTEKS KETATANEGARAAN DI INDONESIA - M Jeffri Arlinandes Chandra (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2018)
Abstract: Regional autonomy provides opportunities for each region to make a regional regulation by prioritizing the needs and desires of the people currently needed. Indonesian society is known as its Multicultural so that in determining regional rules it will concern the values, systems, culture, habits, and politics they hold. The existence of multiculturalism has developed a Regional Regulation that reflects its regionalism, for example, based on customs, culture and regional systems, Sharia Regional Regulations in Aceh and Sharia Nuanced Regulations in developing Indonesia. The rise of regional regulations has led to many pros and cons in society and even among politicians. The anti-sharia regulation was launched by the PSI in 3 main party missions. Significant differences between sharia regulations that apply in Aceh with sharia-nuanced local regulations which are mostly born in autonomous regions in Indonesia conclude that whether such regulations are constitutional and whether it is certain that every sharia or sharia-based regional regulation will always be a discriminatory regional regulation and will lead to intolerance for religious people.Keywords: Autonomy, Regional Regulation, Syari'ah.